If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = 2x + 7 Reorder the terms: 19 = 7 + 2x Solving 19 = 7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 19 + -2x = 7 + 2x + -2x Combine like terms: 2x + -2x = 0 19 + -2x = 7 + 0 19 + -2x = 7 Add '-19' to each side of the equation. 19 + -19 + -2x = 7 + -19 Combine like terms: 19 + -19 = 0 0 + -2x = 7 + -19 -2x = 7 + -19 Combine like terms: 7 + -19 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| k+n=x | | (z-5)(z+4)=36 | | 2x+7y=-19 | | ln(x)=.33 | | (X+3)/(4x-5) | | 7/5/8 | | 15z^2-53z=28 | | m-33=-18 | | 3(3x-9)/2=5(9x/3)/4 | | 6/11x=128 | | h(t)=20-16tsquared+32t | | 2(4x+5)=35 | | 6x+6=4-bracket(5x-4) | | B^2+6n+8=0 | | 5(x+4)+2=47 | | 210+344= | | 4(x+1)-2x=-4 | | 51=9-7x | | 4c-6=6c+14 | | -5x-6=-46 | | 98.31/49.1/4 | | y=-1(0)+8 | | 3(0)-9y=9 | | 32x-(3x^2)=-35 | | 9x+24=-7x-8 | | -3(0)+4y=-12 | | -3x+4(0)=-12 | | -11x+129=-x-3+2x | | 2(-7)+5(3)=1 | | .5x+3=-10 | | -7x+9=2x | | 2(-4)+5(1)=1 |